IDENTIFICATION OF GROWTH HORMONE GENE OF Pangasionodon hypophthalmus - Raden Roro Sri Pudji Sinarni Dewi; Agus Oman Sudrajat; Alimuddin Alimuddin; Komar Sumantadinata (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2009)
Identification of growth hormone (GH) gene in a target fish is the first step in the construction of “all fish genes transfer vector” to generate transgenic fish. The research was done to identify and characterize the GH gene of Pangasionodon hypophthalmus. There were several activities performed in identifying the GH gene: RNA extraction, cDNA synthesis, PCR amplification, and DNA fragment isolation. The characterizations were done using the nucleotide sequencing engine ABIPRISM 3100. The results were then analyzed using BLASTN/P and GENETYX version 7 program. The full-length GH gene of P. hypophthalmus was 1151 bp in length, coding for an open reading frame (ORF) of 603 bp. The 5’ and 3’ untranslated regions of the GH gene were 22 bp and 526 bp long, respectively. The GH gene of P. hypophthalmus had some common characteristics that are owned by GH genes, such as single tryptophan residue (W) on the 104th amino acid, 5 cysteine residues (C) on the amino acid 71, 135, 173, 190, and 198 and a motif of Asn-Xaa-Thr on C terminus which is the potential location for N-linked glycosilation. Polyadenylation signal (aataaa) was on the 14 bp at the upstream of polyadenylation location. Growth hormone of P. hypophthalmus consisted of over 200 amino acids from GH cDNA deduction. The highest proportion of amino acid composition was leusin (14%) while the lowest was tryptophan (0.5%).